2021
DOI: 10.3390/s21248261
|View full text |Cite
|
Sign up to set email alerts
|

Wearable GPS and Accelerometer Technologies for Monitoring Mobility and Physical Activity in Neurodegenerative Disorders: A Systematic Review

Abstract: Neurodegenerative disorders (NDDs) constitute an increasing global burden and can significantly impair an individual’s mobility, physical activity (PA), and independence. Remote monitoring has been difficult without relying on diaries/questionnaires which are more challenging for people with dementia to complete. Wearable global positioning system (GPS) sensors and accelerometers present a cost-effective and noninvasive way to passively monitor mobility and PA. In addition, changes in sensor-derived outcomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 75 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…Technologies to support older adults and their caregivers at home is an area of strong growth for design. Policy makers, providers, and family caregivers are looking to technological solutions and investing in artificial intelligence (AI) and other technologies that monitor activity and safety of older adults, with a particular focus on Alzheimer’s disease and related dementias (e.g., the AAL Joint Platform of the European Union and AGE-WELL Initiative in Canada) [ 25 , 69 , 91 , 127 , 129 , 138 ]. In the U.S., health care payment systems including Medicaid are now beginning to cover a range of technologies that have remote monitoring functions [ 17 , 28 ], foretelling significant growth as lack of third party reimbursement had impeded startups in the aging space [ 19 , 129 ].…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies to support older adults and their caregivers at home is an area of strong growth for design. Policy makers, providers, and family caregivers are looking to technological solutions and investing in artificial intelligence (AI) and other technologies that monitor activity and safety of older adults, with a particular focus on Alzheimer’s disease and related dementias (e.g., the AAL Joint Platform of the European Union and AGE-WELL Initiative in Canada) [ 25 , 69 , 91 , 127 , 129 , 138 ]. In the U.S., health care payment systems including Medicaid are now beginning to cover a range of technologies that have remote monitoring functions [ 17 , 28 ], foretelling significant growth as lack of third party reimbursement had impeded startups in the aging space [ 19 , 129 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…There is particular excitement about the potential capability of detecting cognitive change using predictive linguistic markers [ 18 , 112 ], which involves audio capture in the home. Location tracking is becoming ubiquitous [ 25 , 48 ], and the problem of social isolation during COVID is further spurring the evolution of telepresence [ 64 , 87 ]. These three categories of technologies represent distinct types of data collection that may be carried out passively with little room for direct control by the older adult.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The progression of PD also makes it important to look at PA over time in the same cohorts of individuals, and how it affects HRQOL, including falls and depression. The data acquired from sensors, such as accelerometers, have increased as the cost of these devices has progressively decreased [ 73 , 74 , 75 ], but lack standardization and links to health-related measures. One study found that involuntary movements may increase the measures of PA [ 76 ], and may need to be factored in.…”
Section: Physical Activity Measures Among People With Condition-speci...mentioning
confidence: 99%
“…Therefore, there is a need for the development of accurate, reliable and sensitive tools for the quanti cation of gait and mobility in real-life (8,9). Digital health technology, including body-worn or wearable devices (WD), offers a way forward by providing digital outcomes to remotely measure and monitor gait (10,11), a fundamental component of mobility (12,13). Nonetheless, due to several persisting challenges in this eld, current tools and techniques are still in their infancy.…”
Section: Introductionmentioning
confidence: 99%